What Do the Hospital Pharmacists Think about the Quality of Pharmaceutical Care Services in a Pakistani Province? A Mixed Methodology Study. (8th January 2015) - Murtaza, Ghulam; Kousar, Rozina; Azhar, Saira; Khan, Shujaat Ali; Mahmood, Qaisar
Abstract : The objective of this study was to evaluate the perception of hospital pharmacists regarding quality of pharmaceutical care services in Khyber Pakhtunkhwa (KPK) Province, Pakistan, through qualitative as well as quantitative approach. For qualitative study, snow ball sampling technique was used. In quantitative part, a cross-sectional study was conducted in 112 hospital pharmacists (out of 128 accessed ones) from both private and public hospitals in six major divisions (divisions are the third tier of government in Pakistan, between the provinces and districts) of KPK. The qualitative study yielded five major themes during thematic analysis: (a) patients reporting, (b) lack of patient counseling, (c) lack of participation in health awareness programs, (d) pharmacists reducing the prescribing errors, and (e) insufficient number of pharmacists. A great proportion (67.9%) of the pharmacists was unsatisfied with their participation in health awareness programs. Findings of both phases revealed that hospital pharmacists in Pakistan are not actively participating in the provision of pharmaceutical care services. They are facing various hurdles for their active participation in patient care; major obstacles include the unavailability of sufficient number of pharmacists, lack of appropriate time for patient counseling, and poor relationship between pharmacists and other health care providers.